PIRLS RESEARCH PROCEDURE AND STANDARDIZATION AND RESEARCH TOOLS - Hilola Majidova (American Journals, 2023)
The article describes the requirements, advantages of the international assessment program PIRLS, its procedure and research tools.
Keywords: PIRLS research, IEA, reading order, standardization, research tools, etc.